Sequence-specific assembly of FtsK hexamers establishes directional translocation on DNA. - Graham, J; Sherratt, D; Szczelkun, MD (2010)
FtsK is a homohexameric, RecA-like dsDNA translocase that plays a key role in bacterial chromosome segregation. The FtsK regulatory γ-subdomain determines directionality of translocation through its interaction with specific 8 base pair chromosomal sequences [(KOPS); FtsK Orienting/Polarizing Sequence(s)] that are cooriented with the direction of replication in the chromosome. We use millisecond-resolution ensemble translocation and ATPase assays to analyze the assembly, initiation, and translocation of FtsK. We show that KOPS are used to initiate new translocation events rather than reorient existing ones. By determining kinetic parameters, we show sigmoidal dependences of translocation and ATPase rates on ATP concentration that indicate sequential cooperative coupling of ATP hydrolysis to DNA motion. We also estimate the ATP coupling efficiency of translocation to be 1.63-2.11 bp of dsDNA translocated/ATP hydrolyzed. The data were used to derive a model for the assembly, initiation, and translocation of FtsK hexamers.